2014
DOI: 10.1038/srep05396
|View full text |Cite
|
Sign up to set email alerts
|

Rapid generation of mouse models with defined point mutations by the CRISPR/Cas9 system

Abstract: Introducing a point mutation is a fundamental method used to demonstrate the roles of particular nucleotides or amino acids in the genetic elements or proteins, and is widely used in in vitro experiments based on cultured cells and exogenously provided DNA. However, the in vivo application of this approach by modifying genomic loci is uncommon, partly due to its technical and temporal demands. This leaves many in vitro findings un-validated under in vivo conditions. We herein applied the CRISPR/Cas9 system to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
187
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(200 citation statements)
references
References 13 publications
11
187
2
Order By: Relevance
“…Wang et al [8] reported the efficient production of mice with nucleotide substitutions, in which two nucleotides were converted at Tet1 (GC>AT substitution) and Tet2 (TA>AT substitution) loci by microinjection of ssODN, sgRNAs, and Cas9 mRNA in fertilized eggs. Inui et al [9] also showed induction of point mutations in the Sf1 (C>T substitution) gene by this strategy. Reports showing the production of animals with nucleotide substitutions are summarized in Table 1.…”
Section: Hdr-mediated Production Of Nucleotide Substitution In Micementioning
confidence: 99%
“…Wang et al [8] reported the efficient production of mice with nucleotide substitutions, in which two nucleotides were converted at Tet1 (GC>AT substitution) and Tet2 (TA>AT substitution) loci by microinjection of ssODN, sgRNAs, and Cas9 mRNA in fertilized eggs. Inui et al [9] also showed induction of point mutations in the Sf1 (C>T substitution) gene by this strategy. Reports showing the production of animals with nucleotide substitutions are summarized in Table 1.…”
Section: Hdr-mediated Production Of Nucleotide Substitution In Micementioning
confidence: 99%
“…CRISPR/Cas9-induced genome editing was recently performed in ␀-Thal iPSCs using a piggyBac or donor vector as the repair template (15,16). Previous studies demonstrated that single strand oligodeoxynucleotides (ssODNs) could be used as templates to generate point mutations and short sequence insertions in human cells and animal models (21)(22)(23); however, no studies have been reported showing the efficacy of using ssODNs as a template to correct the HBB mutation in ␀-Thal patient-specific iPSCs.…”
mentioning
confidence: 99%
“…With a CRISPR approach, injection of an sgRNA and Cas9 mRNA or protein into the one-cell embryo creates germline knockout mice in one generation-4 weeks. 31 Moreover, multiple genes can be targeted at once, which is impossible using standard approaches. 32 One-step generation of mouse knockins is also possible, but it is less efficient than creating knockouts.…”
Section: Genome Engineering In Model Organismsmentioning
confidence: 99%